2018
DOI: 10.1172/jci95351
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin–mediated immune evasion pathway frequently operates in primary cutaneous melanomas

Abstract: Immunotherapy prolongs survival in only a subset of melanoma patients, highlighting the need to better understand the driver tumor microenvironment. We conducted bioinformatic analyses of 703 transcriptomes to probe the immune landscape of primary cutaneous melanomas in a population-ascertained cohort. We identified and validated 6 immunologically distinct subgroups, with the largest having the lowest immune scores and the poorest survival. This poor-prognosis subgroup exhibited expression profiles consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 79 publications
(118 citation statements)
references
References 63 publications
6
105
3
Order By: Relevance
“…The mechanisms underlying interpatient heterogeneity of immune response in GBM are unclear . β‐catenin‐mediated immune evasion pathways operate in CIC4, the group with the poorest prognosis in melanoma , whereas in this study we found no evidence of CTNNB1 differential expression between CIC2 and CIC4, nor was their mutational burden significantly different. However, GBM arises through various combinations of oncogene and tumour suppressor mutations, and several of these genes regulate tumour immune responses .…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…The mechanisms underlying interpatient heterogeneity of immune response in GBM are unclear . β‐catenin‐mediated immune evasion pathways operate in CIC4, the group with the poorest prognosis in melanoma , whereas in this study we found no evidence of CTNNB1 differential expression between CIC2 and CIC4, nor was their mutational burden significantly different. However, GBM arises through various combinations of oncogene and tumour suppressor mutations, and several of these genes regulate tumour immune responses .…”
Section: Discussioncontrasting
confidence: 75%
“…Indeed, melanoma shows interpatient heterogeneity of immune responses, and regarding melanoma as 'hot' fails to account for this variability. In melanoma, immune heterogeneity impacts upon survival [14] and the success of immunotherapy, with high expression of PD-1, CD8 + T cell infiltration and higher mutational burden associating with response to therapy [9]. We found no evidence for differential survival in GBM according to our CIC classifications, suggesting that the extensive immunosuppressive network removes any impact of immune control on GBM progression.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Nsengimana et al somehow reached a similar conclusion to Spranger et al. This group categorized 703 primary cutaneous melanomas based on their transcriptional profiles . Six clusters were identified, and among those with the worst survival were the ones with a β‐catenin‐high signal.…”
Section: Candidate Signaling Pathways As Potential Targets For Combinmentioning
confidence: 66%